Photochemical analysis for selection of stress tolerant plant - Sung Yung Yoo; Mikyung Lee; Suk Yong Ha; Tae Wan Kim (International Journal on Food, Agriculture and Natural Resources, 2020)
This electronic document is a “live” template and already defin This study was carried out to selection of abiotic stress tolerant plant species of sixty-eight plant species at Hantaek Botanical Garden in Korean using photochemical analysis. Many abiotic stresses have led to a decline in agricultural productivity and the disappearance of ecologically important plant species. Chlorophyll a fluorescence is a powerful tool to measure environmental stress response in plants. The polyphasic OJIP fluorescence transient was used to evaluate the behavior of Photosystem II (PSII) and Photosystem I (PSI) during the entire experiment period (from July to August). The photochemical reaction showed higher maximal chlorophyll fluorescence (Fp) intensity under heat and wet stress in forty-one plant species. In twenty seven plant species, chlorophyll fluorescence intensity showed a significant decrease. In wet stress, the fluorescence parameters related with electron transport on PSII and PSI reduced over twenty percent. As a result of the identifying under heat and wet stress, energy dissipation per reaction center (DIo/RC) was heavily affected. It was clearly indicated that the connectivity between photosynthetic PSII and PSI, i.e. electron transport, was far effective in the selection of stress tolerant plants.